Analisis Keputusan Nasabah Menggunakan Layanan E-Banking Pada Bank Syariah Indonesia Di Kota Langsa - Muhammad Dayyan; Nurjanah; Uci Dinda Ayu Bestari (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
This research aims to analyze e-banking services at Bank Syariah Indonesia, factors that affect customers using e-banking, and the obstacles faced by customers using e-banking. The method used is qualitative descriptive, with 13 respondents. The results showed that Digital services at Bank Syariah Indonesia there are 20 services, where often used by Bank Syariah Indonesia customers are ATMs and mobile banking. Then the factors that affect customers using e-banking are quality, individual factors, social factors, and promotions, while the obstacles experienced by customers are the customer's ability about the use of technology and networks that must be appropriate for the provider.